Prevalence of Psychiatric Diagnoses and Psychiatric Consultation Service Utilization on Inpatient Medical Units. (July 2022) - Reis, Bianca; Tsai, Jenny Hsin-Chun
OBJECTIVE: This practice improvement project sought to determine the prevalence of psychiatric diagnoses among patients admitted to a community hospital's inpatient medical units and which diagnoses were serviced by the hospital's psychiatric consultation service. METHOD: Electronic medical record data on adult patients of five medical units admitted with a psychiatric condition between October 1, 2019, and December 31, 2019, were used. Psychiatric ICD-10 ( International Classification of Diseases, 10th Revision ) codes and diagnosis names extracted were categorized into seven major diagnostic groups. A total of 687 adult patients with 82 psychiatric ICD-10 codes were analyzed using descriptive statistics. RESULTS: Substance-related and addictive disorders were the most prevalent psychiatric diagnoses. Ninety-six percent ( n = 658) of patients residing on medical floors with psychiatric disorders were hospitalized for a principal medical problem. Seventy-three cases received psychiatric consultations during their stay. Sixty percent ( n = 44) of those cases had psychiatric disorders from two or more diagnostic categories. CONCLUSIONS: Multidisciplinary, team-based health care delivery models that include a psychiatric nurse can provide an effective approach to treat patients in community hospitals with multiple psychiatric and medical comorbidities. Hospitals could take a significant role in providing substance use disorder treatment and equipping medical nurses with training to competently care for patients with psychiatric disorders on medical units. Further research into the prevalence and impact of patients with co-occurring and multiple psychiatric diagnoses in community hospitals is needed to implement effective health care delivery models and provide appropriate treatment options in the community.